KEMATANGAN SOSIAL, JENIS KELAMIN, DAN PERSEPSI TENTANG INTERAKSI AYAH DAN IBU - Agustin Rahmawati (University of Merdeka Malang, 2013)
This research aims to find out the relationship between social maturity, sex, and perception of father and mother interaction. The population in this study were male and female students in SMA Untag Surabaya as much 330 students. The sample in this study who has complete parents (father and mother) and living with them as many as 122 students. That used research bottom is Purposive Sampling. The process of data analysis used were Kovarians Analysis Single Way Test. From Anakova Single Way programme were found result Regression Analysis that is available correlation between perception of father and mother interaction and adolescent social maturity as big as F = 68,455 with p = 0,000 (p 0,05). From this analysis were also obtained the value of F = 7,452 with p = 0,007. It means there is differences social maturity between male students and female students. The male students social maturity better than female students social maturity. The mean male students social maturity is 115,294, and the mean female students social maturity is 109,824.